Retail shelf replenishment with item-level RFID tagging. (24th June 2011) - Abdulmalek, Fawaz; Wang, Lin; Norman, Bryan A.; Rajgopal, Jayant
A major priority for large retailers is ensuring that items are on the shelf in sufficient quantities to satisfy all customer demand. In recent years, there has been much interest in the use of radio frequency identification (RFID) technology to track items throughout the supply chain, and in particular, for providing precise and timely shelf level inventory information. We develop a detailed simulation model to study the impact of using RFID for shelf replenishment at a retail facility. The model evaluates scenarios with and without RFID to understand the relative gains, which can then be used to evaluate relevant economic trade-offs.